2010
DOI: 10.1002/jbmr.67
|View full text |Cite
|
Sign up to set email alerts
|

Taking vitamin D with the largest meal improves absorption and results in higher serum levels of 25-hydroxyvitamin D

Abstract: Many patients treated for vitamin D deficiency fail to achieve an adequate serum level of 25-hydroxyvitamin D [25(OH)D] despite high doses of ergo-or cholecalciferol. The objective of this study was to determine whether administration of vitamin D supplement with the largest meal of the day would improve absorption and increase serum levels of 25(OH)D. This was a prospective cohort study in an ambulatory tertiary-care referral center. Patients seen at the Cleveland Clinic Foundation Bone Clinic for the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 9 publications
0
21
2
2
Order By: Relevance
“…• Administration: oral administration of vitamin D provides a faster and better controlled delivery compared with intramuscular preparations, since IM route leads to a sequestration in the muscle and fat with gradual release in the vascular system [65]. Vitamin D is fat soluble and because of this it is also advised to ingest it after the main meal of the day in order to improve intestine absorption [66]. • Periodicity: supplementation dosages can be given in different time intervals to achieve a desired equivalent "daily dose".…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…• Administration: oral administration of vitamin D provides a faster and better controlled delivery compared with intramuscular preparations, since IM route leads to a sequestration in the muscle and fat with gradual release in the vascular system [65]. Vitamin D is fat soluble and because of this it is also advised to ingest it after the main meal of the day in order to improve intestine absorption [66]. • Periodicity: supplementation dosages can be given in different time intervals to achieve a desired equivalent "daily dose".…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…He found that taking vitamin D supplements with largest meal showed 50% improvement in vitamin D absorption. 19 This strategy is respected in our study. Some other factors might also be related to the effectiveness of vitamin D supplement therapy.…”
Section: Resultsmentioning
confidence: 98%
“…It is recommended to expose the hands, arms and face to sunlight for approximately 5-25 min per day, but this is limited during hospitalisation and by other social factors, so supplementation should be prescribed. The recommendation for an adequate supplementation of vitamin D intake for older people is 800-1000 IU per day [8] and it should be taken with main meals [9].…”
Section: 3mentioning
confidence: 99%